Could Stress Contribute to Pain-Related Fear in Chronic Pain? - Elsenbruch, Sigrid; Wolf, Oliver T. (Frontiers in Behavioral Neuroscience, 2015)
Learning to predict pain based on internal or external cues constitutes a fundamental and highly adaptive process aimed at self-protection. Pain-related fear is an essential component of this response, which is formed by associative and instrumental learning processes. In chronic pain, pain-related fear may become maladaptive, drive avoidance behaviors and contribute to symptom chronicity. Pavlovian fear conditioning has proven fruitful to elucidate associative learning and extinction involving aversive stimuli, including pain, but studies in chronic pain remain scarce. Stress demonstrably exerts differential effects on emotional learning and memory processes, but this has not been transferred to pain-related fear. Within this perspective, we propose that stress could contribute to impaired pain-related associative learning and extinction processes and call for interdisciplinary research. Specifically, we suggest to test the hypotheses that (1) extinction-related phenomena inducing a re-activation of maladaptive pain-related fear (e.g., reinstatement, renewal) likely occur in everyday life of chronic pain patients and may alter pain processing, impair perceptual discrimination and favour overgeneralization; (2) acute stress prior to or during acquisition of pain-related fear may facilitate the formation and/or consolidation of pain-related fear memories, (3) stress during or after extinction may impair extinction efficacy resulting in greater reinstatement or context-dependent renewal of pain-related fear; and (4) these effects could be amplified by chronic stress due to early adversity and/or psychiatric comorbidity such as depression or anxiety in patients with chronic pain.